Sleep Patterns and Long-Lasting Risk of Diabetes Mellitus Type 2 in Females with a History of Gestational Diabetes Mellitus - Zulfiqar, Hannan; Malik, Sarwar; Hussain, Shoukat; Khan, Muhammad Akram (Indus Journal of Bioscience Research, 2025)
Background: Gestational diabetes mellitus is a type of hyperglycemia that occurs or is diagnosed during pregnancy. The state of sleep is becoming a crucial public health concern globally. Methodology: It was a prospective cohort study. 38 women having a history of gestational diabetes mellitus participated in the study. The study was carried out at Capital Hospital, Islamabad, for six months from September 2024 to February 2025. Patients who responded to sleep characteristics were also included in the study. Data was analyzed by IBM SPSS version 25. Based on previous literature, a sample of 38 participants was included in the study. The chi-square test was applied to find the association between T2D and sleep quality, and an independent sample t-test was applied to analyze the comparison between health variables and participants with and without T2D. Results: The average age is 37.45 years with SD=5.674, with a range of 30 to 45 years. Most participants, 71.1%, did not have T2D, whereas 28.9% had T2D. Diabetic patients had a substantially higher BMI (M=30.66, SD=1.39) than non-diabetics (M=24.45, SD=1.22; t(36)=13.65, 95% CI (5.29,7.14). Compared to the non-diabetic group (M=91.73, SD=5.74), the diabetic group had higher fasting blood glucose levels (M=121.98, SD=6.74), t(36)=14.01, 95% CI [25.87, 34.63]. None of the 11 participants with T2D had good sleep quality, while 27 without type 2 diabetes reported good sleep. Conclusion: The results show a strong association between T2D and various health factors. Participants with T2D had higher BMI, fasting glucose level, and HbA1c values, along with shorter sleep duration and less physical activity. Poor sleep quality suggests a significant association between sleep quality and type 2 diabetes mellitus (T2D).